65‐1: Maximum Comfortable Luminance of Head Mounted Display under Various Surround Illuminances. Issue 1 (30th May 2018) - Ha, Hyeyoung; Kwak, Youngshin; Kim, Hyosun; Seo, Young-jun; Lee, Seungbae; Jo, Sung-Chan
Abstract : The comfortable luminance of Head Mounted Display (HMD) was investigated under four different surround illuminances. In the psychophysical experiment, participants adapted to the surround illuminance for five minutes and they were asked to answer whether HMD luminance is comfortable or not with the method of constant stimuli. The result demonstrates that the comfortable luminance is increased as the surround illuminance is increased, suggesting the needs of the adaptive luminance control of HMD.